El Excentrico, 1960-12-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
December 20, 1960 [20 de diciembre de 1960]. Ano 11, No 5, Cover has a photograph of a child smiling in awe in a season's greetings card. with headline "Lovely Leticia Graham will enjoy her first Christmas."